2022
DOI: 10.1002/cam4.4751
|View full text |Cite
|
Sign up to set email alerts
|

Progression‐free survival at 3 years is a reliable surrogate for 5‐year overall survival for patients suffering from locally advanced esophageal squamous cell carcinoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…As far as we know, this was the first study to identify PFS-based endpoints systematically in advanced ESCC patients receiving immunotherapy in combination with chemotherapy as 1-L treatment. Previous studies have shown that three-year PFS is a reliable SE of 5-year OS in locally advanced ESCC treated with definitive RT; when treating resectable ESCC and esophageal adenocarcinoma (EAC) and gastroesophageal junction (GEJ) cancer, HR PFS can be used in neoadjuvant, perioperative, or adjuvant settings as a substitute for HR OS ; in addition, in neoadjuvant RCTs of gastric carcinoma(GC) and GEJ adenocarcinoma, event-free survival (EFS) could serve as a SE [ 35 37 ]. However, in the immune-oncology (IO) era, due to the special response patterns of Immuno-checkpoint inhibitors (ICIs) such as pseudoprogression and delayed response, whether the traditional SE for OS is applicable to IO trials is controversial [ 38 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, this was the first study to identify PFS-based endpoints systematically in advanced ESCC patients receiving immunotherapy in combination with chemotherapy as 1-L treatment. Previous studies have shown that three-year PFS is a reliable SE of 5-year OS in locally advanced ESCC treated with definitive RT; when treating resectable ESCC and esophageal adenocarcinoma (EAC) and gastroesophageal junction (GEJ) cancer, HR PFS can be used in neoadjuvant, perioperative, or adjuvant settings as a substitute for HR OS ; in addition, in neoadjuvant RCTs of gastric carcinoma(GC) and GEJ adenocarcinoma, event-free survival (EFS) could serve as a SE [ 35 37 ]. However, in the immune-oncology (IO) era, due to the special response patterns of Immuno-checkpoint inhibitors (ICIs) such as pseudoprogression and delayed response, whether the traditional SE for OS is applicable to IO trials is controversial [ 38 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the correlation between the clinical endpoint OS and potential short-term outcome of interest, such as ORR, MRD-negative CR, PFS, or EFS [19,20], can accelerate the development of new drugs. This approach has been identified in several malignant hematological tumors [21], we similarly assessed the correlation in the included data.…”
Section: Correlation Between Orr Mrd-negative Cr Pfs and Osmentioning
confidence: 99%
“…However, a considerable number of EC patients still develop metastasis and recurrence after surgery. The 5-year survival rate of EC patients after surgery is <20% ( 8 ). EC seriously endangers the health of people all over the world.…”
Section: Introductionmentioning
confidence: 99%